Side effects of the Pfizer BioNTech vaccine in health workers of a hospital in the southeast of Mexico - Jesús Arturo Ruiz-Quiñones; Víctor Manuel Narváez-Osorio; Oscar Antonio Ulín-Tejeda; Oscar Israel Flores-Barrientos; Samuel Suárez-Méndez; Guadalupe del Carmen Baeza-Flores (Journal of Infection in Developing Countries)
Introduction: The goal of this study was to evaluate the side effects of application of the Pfizer BioNTech vaccine on the workers at a Mexican hospital.